Successful Recruitment to Qualitative Research: A Critical Reflection - Kelly A. Negrin; Susan E. Slaughter; Sherry Dahlke; Joanne Olson (International Journal of Qualitative Methods, 2022)
Recruitment to qualitative research is an important methodological consideration. However, the process of recruitment is under-communicated in qualitative research articles and methods textbooks. A robust recruitment plan enhances trustworthiness and overall research success. Although recruitment has recently received increased attention in the qualitative methodology literature, a more nuanced understanding is required. We realized successful recruitment to our focused ethnographic inquiry. Numerous nurse educators, researchers, and administrators volunteered within three months of study initiation. Using Gibbs’ Reflective Cycle, we conducted a critical reflection on the recruitment log and participant interview data to surface factors contributing to our success. This article offers our insights into the facilitators of successful recruitment. Our reflection revealed four themes contributing to successful enrollment: (a) laying the groundwork, (b) recruitment plan, (c) building rapport, and (d) participant motivations. Two new recruitment strategies accounted for over 60% of our sample. Reporting on successful strategies for recruiting participants to qualitative research and specifying participants’ motivations to volunteer, from their perspective, make important contributions to the recruitment literature. Our article offers guidance to qualitative researchers pursuing successful recruitment. Additional research is required to evaluate the relative influence of various recruitment strategies.